2013
DOI: 10.1073/pnas.1306358110
|View full text |Cite
|
Sign up to set email alerts
|

CRL4A-FBXW5–mediated degradation of DLC1 Rho GTPase-activating protein tumor suppressor promotes non-small cell lung cancer cell growth

Abstract: DLC1 encodes a RhoA GTPase-activating protein and tumor suppressor lost in cancer by genomic deletion or epigenetic silencing and loss of DLC1 gene transcription. We unexpectedly identified nonsmall cell lung cancer (NSCLC) cell lines and tumor tissue that expressed DLC1 mRNA yet lacked DLC1 protein expression. We determined that DLC1 was ubiquitinated and degraded by cullin 4A-RING ubiquitin ligase (CRL4A) complex interaction with DDB1 and the FBXW5 substrate receptor. siRNA-mediated suppression of cullin 4A,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 40 publications
2
62
0
Order By: Relevance
“…Another recent study identified the serine-threonine kinase CKD5 to phosphorylate DLC1 on multiple residues within the N-terminus, thereby inducing an open conformation that leads to activation of GAP function [80]. Finally, GAP regulation can be switched off irreversibly by ubiquitindependent protein degradation of DLC1, adding an additional layer of complexity to the post-translational regulation of DLC1 [38]. However, none of these studies has been able to define the specific DLC1 pool that is subject to such regulation and determine the biological context during which this occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study identified the serine-threonine kinase CKD5 to phosphorylate DLC1 on multiple residues within the N-terminus, thereby inducing an open conformation that leads to activation of GAP function [80]. Finally, GAP regulation can be switched off irreversibly by ubiquitindependent protein degradation of DLC1, adding an additional layer of complexity to the post-translational regulation of DLC1 [38]. However, none of these studies has been able to define the specific DLC1 pool that is subject to such regulation and determine the biological context during which this occurs.…”
Section: Discussionmentioning
confidence: 99%
“…The GAP activity of several RhoGAPs is regulated by phosphorylation (TABLE 2). A number of phosphorylation sites have been characterized on the RhoGAP DLC1 (deleted in liver cancer 1), the product of a tumour suppressor gene that is lost in several cancers through either epigenetic silencing or gene deletion 99 . PKA-mediated phosphorylation of DLC1 on Ser549 induces its homodimerization, which increases its RhoGAP activity 100 .…”
Section: Regulation Of Gapsmentioning
confidence: 99%
“…Ubiquitylation of DLC1 by a CUL4 FBXW5 ubiquitin ligase complex leads to its degradation in nonsmall-cell lung cancer cell lines 99 . This provides another mechanism, in addition to gene deletion or epigenetic silencing, to remove this tumour suppressor.…”
Section: Regulation Of Gapsmentioning
confidence: 99%
“…However, FBXW5 was recently reported to control the stability of deleted in liver cancer 1 (DLC1; also known as RHO GTPase-activating protein 7) 122 and tuberous sclerosis 2 (TSC2) 123 tumour suppressors (see Supplementary information S2 (table)), which suggests a possible oncogenic role for FBXW5, but this requires knockout or knock-in mouse models for further validation.…”
Section: Undetermined But Probable Functions In Cancermentioning
confidence: 99%